Impact of Different Cofactors on Naturally Acquired Human Papillomavirus Antibody Levels Among Unvaccinated Pregnant Women - Kirjavainen, Laura (Mary Ann Liebert, 2025)
Human papillomavirus (HPV) infections are common, transmitted by sexual and nonsexual routes. The present case-control setting was designed to examine potential cofactors associated with either persistently low or high HPV-antibody levels. The study subjects were from the Finnish HPV Family cohort of 329 baseline pregnant, non-HPV-vaccinated women, who were sampled for genital and oral HPV-DNA and HPV serology at baseline, and at 12, 24, and 36 months. Antibodies to the L1 major capsid protein of HPV 6, 11, 16, 18, and 45 were analyzed by multiplex HPV serology and HPV genotyping was performed. This study included 59 women, 23 women with persistently low (<200 median fluorescence intensity [MFI]) and 36 women with persistently high and always positive (>200 MFI) levels of these antibodies for all five HPV genotypes. Potential HPV-associated covariates were derived from detailed questionnaires. Only cofactors other than detected HPV genotype significantly impact on the levels of natural HPV antibodies. A higher number of past sexual partners or a history of diagnosed genital warts were significant covariates of high HPV antibody levels (p = 0.023 and p = 0.043, respectively). Of interest, women with a history of allergies presented with low levels of HPV antibodies (p = 0.03), potentially exposing these women to an increased risk of future HPV-related diseases that merit closer surveillance.